2023
DOI: 10.3390/nano13091496
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gas Type, Oil, Salts and Detergent on Formation and Stability of Air and Carbon Dioxide Bubbles Produced by Using a Nanobubble Generator

Abstract: Recent developments in ultrafine bubble generation have opened up new possibilities for applications in various fields. Herein, we investigated how substances in water affect the size distribution and stability of microbubbles generated by a common nanobubble generator. By combining light scattering techniques with optical microscopy and high-speed imaging, we were able to track the evolution of microbubbles over time during and after bubble generation. Our results showed that air injection generated a higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…This observation is consistent with previous studies. 41,42,50 The nanobubble number density initially increased at a low concentration of NaCl. This can be attributed to the so-called "salting out" effect, which reduces the gas solubility in the bulk liquid, thereby inducing nanobubble generation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This observation is consistent with previous studies. 41,42,50 The nanobubble number density initially increased at a low concentration of NaCl. This can be attributed to the so-called "salting out" effect, which reduces the gas solubility in the bulk liquid, thereby inducing nanobubble generation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…SDS has also demonstrated effectiveness in stabilizing CO 2 MBs within oil-in-water emulsions. Studies have shown that higher SDS concentrations correspond to increased MB stability . Lu et al employed SDS in combination with PVA and graphene oxide to stabilize CO 2 bubbles encapsulated in micrometer-sized water droplets during an evaporation process, resulting in thin-shell particles containing CO 2 .…”
Section: Materials Requiredmentioning
confidence: 99%